Polarizing film and its manufacturing method

By using boron-containing compounds to crosslink PVA molecular chains with controlled boron distribution, the polarizing film achieves high polarization performance and transmittance, overcoming previous limitations in LCDs.

JP7610576B2Active Publication Date: 2025-01-08KURARAY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022507273
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-13
Filing Date
2021-03-11
Publication Date
2025-01-08
Estimated Expiration
2041-03-11

AI Technical Summary

Technical Problem

Existing polarizing films face challenges in achieving high polarization performance and transmittance due to issues with PVA stretchability and iodine dye decomposition, leading to insufficient light extraction efficiency in high-definition LCDs.

Method used

A polarizing film with specific boron-containing compounds, such as monoboronic acid, is used to crosslink PVA molecular chains, with precise control of boron element content and distribution to enhance orientation and suppress iodine dye decomposition, resulting in high polarization performance and transmittance.

Benefits of technology

The film achieves high polarization performance and transmittance, addressing the limitations of previous methods and meeting the demands of high-definition LCDs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610576000007
    Figure 0007610576000007
  • Figure 0007610576000008
    Figure 0007610576000008
  • Figure 0007610576000001
    Figure 0007610576000001
Patent Text Reader

Abstract

The present invention is a polarizing film, comprising a polyvinyl alcohol (A), at least one type of boron-containing compound (B) chosen from the group consisting of monoboronic acids represented by formula (I) and compounds that can be converted into such a monoboronic acid in the presence of water, and boric acid (C), wherein the elemental boron content (bt) originating from the boron-containing compound (B) is 0.3–2.0% by mass, the total elemental boron content (T) is 3.0–7.0% by mass, the ratio (bt / T) of (bt) to (T) is 0.10–0.30, and, within a range inward from at least one surface to 7.5% of the entire thickness, the elemental boron concentration (bo) derived from the boron-containing compound (B) is 2.2–10.0% by molecules. This polarizing film has high polarization performance and high transmittance. [In formula (I), R1 is a monovalent aliphatic group having a carbon number of 1–20, and R1 and the boronic acid group are linked by a boron–carbon bond.]
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing film and a method for producing the same. [Background technology]

[0002] Polarizing plates, which have the function of transmitting and blocking light, are a basic component of liquid crystal displays (LCDs) along with liquid crystals, which change the polarization state of light. In order to prevent the polarizing film from fading or shrinking, many polarizing plates have a structure in which a protective film such as a triacetate cellulose (TAC) film is laminated onto the surface of the polarizing film. The polarizing film that constitutes the polarizing plate is a matrix made of a uniaxially stretched polyvinyl alcohol film (hereinafter, "polyvinyl alcohol" may be referred to as "PVA") to which an iodine-based dye (I 3‐ or I 5‐ The mainstream is those that adsorb

[0003] LCDs are used in a wide range of applications, including small devices such as calculators and watches, smartphones, laptops, LCD monitors, LCD color projectors, LCD TVs, in-car navigation systems, and measuring instruments used both indoors and outdoors. In recent years, 4K and 8K LCDs have been put to practical use, and while LCDs are becoming increasingly high-definition, the decrease in light extraction efficiency due to the decrease in aperture ratio has become an issue. For this reason, there is a demand for polarizing films with high polarization performance and high transmittance to compensate for the decrease in light extraction efficiency caused by the decrease in aperture ratio.

[0004] As a method for obtaining a polarizing film with high polarizing performance, a method using PVA with a high polymerization degree is known (for example, Patent Document 1). However, when PVA with a high polymerization degree is used, there is a problem that the stretchability of the PVA film decreases, and therefore the yield of the polarizing film decreases.

[0005] Also known is a method of treating a polarizing film with a reducing agent to decompose unnecessary iodine-based dyes (e.g., Patent Document 2). However, unless the concentration of the reducing agent is strictly controlled, the iodine-based dyes are decomposed more than necessary, making this method difficult to implement industrially.

[0006] Recently, a method of using an aqueous solution of boronic acid has been developed to crosslink PVA molecular chains in a polarizing film. For example, Patent Document 3 describes that a polarizing film with excellent wet heat resistance can be obtained by immersing a PVA film after uniaxial stretching in an aqueous solution (fixing treatment bath) containing a boronic acid such as methylboronic acid or 1,4-butanediboronic acid and potassium iodide. In addition, Patent Documents 4 and 5 describe that a polarizing film with excellent wet heat resistance or a polarizing film with high polarizing performance and small shrinkage force at high temperatures can be obtained by treating a PVA film with a monoboronic acid to impart hydrophobicity.

[0007] However, the polarizing performance of the polarizing films described in Patent Documents 3 to 5 was still insufficient in some cases to meet the demand for higher definition in electronic devices. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 01-084203 [Patent Document 2] Patent Publication No. 2013-156621 [Patent Document 3] WO2018 / 021274 [Patent Document 4] KR10-2015-0052777 [Patent Document 5] WO2019 / 146677 Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention has been made to solve the above problems, and an object of the present invention is to provide a polarizing film having high polarizing performance and high transmittance, and a method for producing the same. [Means for solving the problem]

[0010] As a result of extensive research, the present inventors have found that in order to obtain a polarizing film with high polarizing performance and high transmittance, it is important to adjust the amounts and ratios of boric acid (C) and boron-containing compound (B) used for crosslinking PVA molecular chains in the polarizing film within appropriate ranges, and to have a relatively large amount of boron-containing compound (B) present near the surface of the polarizing film.

[0011] The present invention relates to [1] A polarizing film comprising PVA (A), at least one boron-containing compound (B) selected from the group consisting of monoboronic acids represented by the following formula (I) and compounds that can be converted to the monoboronic acids in the presence of water, and boric acid (C), wherein the boron element content (b t ) is 0.3 to 2.0 mass%, the total boron element content (T) is 3.0 to 7.0 mass%, and (b t ) ratio (b t / T) is 0.10 to 0.30, and the boron element concentration (b o ) is 2.2 to 10.0 atomic %; [ka] [In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 and the boronic acid group are connected by a boron-carbon bond. [2] The boron element concentration (b i) is 0.5 to 2.0 atomic %, and the boron element concentration (c i The polarizing film of [1], wherein the content of ZnO is 3.5 to 8.0 atomic %; [3] The boron element concentration (c i ) relative to the boron concentration (b i ) ratio (b i / c i The polarizing film according to [1] or [2], wherein the refractive index is 0.01 to 0.25; [4] A boron element concentration (c ) derived from boric acid (C) in a range of up to 7.5% of the total thickness from at least one surface to the inside of the polarizing film. o The polarizing film of any one of [1] to [3], wherein the content of ZnO is 3.3 to 7.8 atomic %; [5] The boron element concentration (b) derived from the boron-containing compound (B) in the range of up to 7.5% of the total thickness from at least one surface to the inside of the polarizing film. o ) is the boron element concentration (b i ) any of the polarizing films [1] to [4]; [6] A boron element concentration (c ) derived from boric acid (C) in a range of up to 7.5% of the total thickness from at least one surface to the inside of the polarizing film. o ) is the boron element concentration (c i ) any of the polarizing films [1] to [5]; [7]R 1 The polarizing film of any one of [1] to [6], wherein [8]R 1 the polarizing film according to any one of [1] to [7], wherein [9]R 1 The polarizing film of any one of [1] to [8], wherein the carbon number is 2 to 5;

[10] A polarizing film according to any one of [1] to [9], which has a transmittance of 42% or more when the polarization degree is 99.9% or more;

[11] The method for producing a polarizing film according to any one of [1] to

[10] , comprising a dyeing treatment of dyeing a polyvinyl alcohol film with a dichroic dye and a stretching treatment of uniaxially stretching the film, further comprising a treatment of immersing the film in an aqueous solution containing a boric acid crosslinker, and then immersing the film in an aqueous solution containing 1.5 to 5.0 mass% of a boron-containing compound (B) at 35 to 80°C. Effect of the Invention

[0012] The polarizing film of the present invention has high polarizing performance and high transmittance, and the production method of the present invention makes it possible to easily produce such a polarizing film. [Brief description of the drawings]

[0013] [Figure 1] 1 is a schematic diagram showing a cross section in the thickness direction of a polarizing film of the present invention. [Diagram 2] 1 is a 1H-NMR chart of the polarizing film obtained in Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] <Polarizing film> The polarizing film of the present invention is a polarizing film comprising PVA (A), at least one boron-containing compound (B) selected from the group consisting of monoboronic acids represented by the following formula (I) and compounds that can be converted to the monoboronic acids in the presence of water, and boric acid (C), wherein the boron element content (b t ) is 0.3 to 2.0 mass%, the total boron element content (T) is 3.0 to 7.0 mass%, and (b t ) ratio (b t / T) is 0.10 to 0.30, and the boron element concentration (b o) is 2.2 to 10.0 atomic %.

[0015] [ka]

[0016] [In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 and the boronic acid group are connected by a boron-carbon bond.

[0017] In this way, the total boron element content (T) in the polarizing film and the boron element content (b t ) and their ratios are within a specific range, and further, the boron element concentration (b o ) in a specific range, a film with high polarizing performance and high transmittance can be obtained. The reason for this is that the presence of a relatively large amount of the boron-containing compound (B) on the surface of the polarizing film suppresses the elution of boric acid (C) from the inside. This is thought to be because the relaxation of the orientation of the PVA in the center of the polarizing film is suppressed, and the boron-containing compound (B) removes unnecessary iodine-based dye from the surface of the polarizing film.

[0018] Usually, when a boric acid crosslinked PVA film is immersed in an aqueous solution of a boron-containing compound (B), the reaction of replacing boric acid (C) with the boron-containing compound (B) proceeds from the surface of the PVA film. In order to make the boron-containing compound (B) present in a relatively large amount on the surface of the PVA film, it is important to accelerate the replacement reaction between the boric acid (C) on the surface of the PVA film and the boron-containing compound (B) by immersing the PVA film in an aqueous solution of the boron-containing compound (B) at a relatively high concentration and temperature, as described below. When the concentration of the boron-containing compound (B) is low, the elution of boric acid (C) proceeds preferentially over the adsorption of the boron-containing compound (B). In this case, the boric acid (C) is eluted to the center of the PVA film, and the orientation of the PVA is relaxed, making it difficult to obtain a polarizing film with high polarization performance and high transmittance. In addition, the rigidity of the polarizing film may decrease, causing wrinkles. When the aqueous solution of the boron-containing compound (B) is at a low temperature, boric acid (C) is difficult to dissolve, and the boron-containing compound (B) is not adsorbed. In this case, the effect of improving the polarization performance by adding the boron-containing compound (B) is insufficient, and a polarizing film with high polarization performance and high transmittance cannot be obtained. On the other hand, when a boric acid crosslinked PVA film is immersed in an aqueous solution of the boron-containing compound (B) at a relatively high concentration and at a high temperature, the substitution reaction proceeds quickly on the surface of the PVA film. As a result, the relaxation of the orientation of PVA in the center of the PVA film is suppressed, and unnecessary iodine-based dyes on the surface of the PVA film are removed by the boron-containing compound (B), so that a polarizing film with high polarization performance and high transmittance is obtained.

[0019] The boron-containing compound (B) in the polarizing film of the present invention is at least one selected from the group consisting of monoboronic acids represented by the above formula (I) and compounds that can be converted to the monoboronic acids in the presence of water. 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 and the boronic acid group are connected by a boron-carbon bond.

[0020] A monoboronic acid is a compound represented by the above formula (I), and has one boronic acid group [-B(OH)2] in one molecule. The boronic acid group has a structure in which a boron atom to which two hydroxyl groups are bonded is bonded to a carbon atom. In the compound represented by formula (I), R 1 and the boronic acid group are connected by a boron-carbon bond. In boric acid [B(OH)3], the boron atom is bonded to three hydroxyl groups, whereas the boronic acid group has a boron-carbon bond. A representative example of a boron-containing group that can be converted to a boronic acid group in the presence of water is the boronic acid ester group described below, but is not limited thereto.

[0021] The hydroxyl group in the boronic acid group contained in the monoboronic acid can form an ester with an alcohol, just like the hydroxyl group in boric acid. The following formula (II) shows a boronic acid with one molecule of alcohol (R 2 In this case, when the boronic acid group is bonded to the hydroxyl group of PVA (A), R in formula (II) is a monoboronic acid monoester. 2 is a PVA chain, and a carbon-containing group is bonded to the PVA chain via a boron atom.

[0022] [ka]

[0023] The following formula (III) represents a compound in which two molecules of alcohol (R 2 This is an example of a monoboronic acid diester in which the boronic acid group is reacted with the hydroxyl group of PVA. Here, when the boronic acid group is bonded to the hydroxyl group of PVA, the two R 2 are both PVA chains.

[0024] [ka]

[0025] Monoboronic acid has two hydroxyl groups that can react with the hydroxyl groups of PVA to form esters, resulting in moderate cross-linking of the PVA chains. Although the reason is unclear, this cross-linking enhances the orientation of the PVA and destabilizes and reduces unnecessary iodine-based dyes, improving the polarization performance of the polarizing film, which is thought to result in a polarizing film with high polarization performance and high transmittance.

[0026] In formula (I), R 1 R is a monovalent aliphatic group having 1 to 20 carbon atoms. 1 By having an appropriate length, the solubility of the boron-containing compound (B) in water and the reactivity with the hydroxyl group of PVA can be controlled. From the viewpoint of obtaining a polarizing film with excellent optical performance due to good adsorption to the polarizing film, R 1 The number of carbon atoms in R is preferably 10 or less, more preferably 6 or less, and even more preferably 5 or less. On the other hand, from the viewpoint of a particularly excellent balance between the optical performance and the shrinkage force of the polarizing film, R 1 The number of carbon atoms is preferably 2 or more, and more preferably 3 or more.

[0027] In formula (I), R 1 is a monovalent aliphatic group, R 1 and the boronic acid group are connected by a boron-carbon bond. 1 R may be a saturated or unsaturated aliphatic group, but the former is preferred. 1 By being a saturated aliphatic group, coloration of the resulting polarizing film is suppressed and durability is improved. 1 By being a saturated aliphatic group, the orientation of the dichroic dye is improved, and the optical performance is further improved. Note that an unsaturated aliphatic group is an aliphatic group having a structure containing multiple bonds with a bond order of 2 or more, such as a carbon-carbon double bond, a carbon-carbon triple bond, a carbon-oxygen double bond, a carbon-nitrogen double bond, a nitrogen-nitrogen double bond, or a carbon-sulfur double bond, and a saturated aliphatic group is an aliphatic group having only a single bond structure. 1Examples of monoboronic acids in which is a saturated aliphatic group include methylboronic acid, ethylboronic acid, propylboronic acid, butylboronic acid, pentylboronic acid, hexylboronic acid, heptylboronic acid, octylboronic acid, nonylboronic acid, decanylboronic acid, undecanylboronic acid, dodecanylboronic acid, tridecylboronic acid, tetradecanylboronic acid, pentadecanylboronic acid, hexadecanylboronic acid, heptadecanylboronic acid, octadecanylboronic acid, nonadecanylboronic acid, icosanylboronic acid and isomers thereof, cyclopropylboronic acid, cyclobutylboronic acid, ethylboronic acid, propylboronic acid, butylboronic acid, pentylboronic acid, hex ...butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butylboronic acid, butyl Boronic acid, cyclopentylboronic acid, cyclohexylboronic acid, cycloheptylboronic acid, cyclooctylboronic acid, cyclononylboronic acid, cyclodecanylboronic acid, cycloundecanylboronic acid, cyclododecanylboronic acid, cyclotridecanylboronic acid, cyclotetradecanylboronic acid, cyclopentadecanylboronic acid, cyclohexadecanylboronic acid, cycloheptadecanylboronic acid, cyclooctadecanylboronic acid, cyclononadecanylboronic acid, cycloicosanylboronic acid and their isomers, 2-oxa-propylboronic acid, 2-oxo ... Subbutylboronic acid, 2-oxa-hexylboronic acid, 2-oxa-heptylboronic acid, 2-oxa-octylboronic acid, 2-oxa-nonylboronic acid, 2-oxa-decanylboronic acid, 2-oxa-undecanylboronic acid, 2-oxa-dodecanylboronic acid, 2-oxa-tridecanylboronic acid, 2-oxa-tetradecanylboronic acid, 2-oxa-pentadecanylboronic acid, 2-oxa-hexadecanylboronic acid, 2-oxa-heptadecanylboronic acid, 2-oxa-octadecanylboronic acid, 2-oxa-nonadecanylboronic acid, 2-oxa- Icosanylboronic acid and its isomers, 2-aza-propylboronic acid, 2-aza-butylboronic acid, 2-aza-hexylboronic acid, 2-aza-heptylboronic acid, 2-aza-octylboronic acid, 2-aza-nonylboronic acid, 2-aza-decanylboronic acid, 2-aza-undecanylboronic acid, 2-aza-dodecanylboronic acid, 2-aza-tridecanylboronic acid, 2-aza-tetradecanylboronic acid, 2-aza-pentadecanylboronic acid, 2-aza-hexadecanylboronic acid, 2-aza-heptadecanylboronic acid, 2-aza-octadecanylboronic acid,2-Aza-nonadecanylboronic acid, 2-aza-icosanylboronic acid and their isomers, 2-phospha-propylboronic acid, 2-phospha-butylboronic acid, 2-phospha-hexylboronic acid, 2-phospha-heptylboronic acid, 2-phospha-octylboronic acid, 2-phospha-nonylboronic acid, 2-phospha-decanylboronic acid, 2-phospha-undecanylboronic acid, 2-phospha-dodecanylboronic acid, 2-phospha-tridecanylboronic acid, 2-phospha-tetradecanylboronic acid, 2-phospha-pentadecanylboronic acid, 2-phospha-hexadecanylboronic acid, 2-phospha-heptadecanylboronic acid, 2-phospha-octadecanylboronic acid, 2-phospha-nonadecanylboronic acid Examples of boronic acid include 2-thia-propylboronic acid, 2-thia-butylboronic acid, 2-thia-hexylboronic acid, 2-thia-heptylboronic acid, 2-thia-octylboronic acid, 2-thia-nonylboronic acid, 2-thia-decanylboronic acid, 2-thia-undecanylboronic acid, 2-thia-dodecanylboronic acid, 2-thia-tridecanylboronic acid, 2-thia-tetradecanylboronic acid, 2-thia-pentadecanylboronic acid, 2-thia-hexadecanylboronic acid, 2-thia-heptadecanylboronic acid, 2-thia-octadecanylboronic acid, 2-thia-nonadecanylboronic acid, 2-thia-icosanylboronic acid and isomers thereof. In addition, examples of the compound that can be converted to the monoboronic acid in the presence of water include salts of the monoboronic acid.

[0028] R 1 may be an aliphatic hydrocarbon group or may contain heteroatoms such as oxygen, nitrogen, sulfur, and halogen. 1 is preferably an aliphatic hydrocarbon group not containing a heteroatom. The aliphatic hydrocarbon group is preferably a straight-chain aliphatic hydrocarbon group not containing a branch. This improves the adsorption to the polarizing film, and enhances the effect of improving the optical performance. 1Specific examples of the boronic acid in which is a straight-chain aliphatic hydrocarbon group include methylboronic acid, ethylboronic acid, n-propylboronic acid, n-butylboronic acid, n-pentylboronic acid, n-hexylboronic acid, n-heptylboronic acid, n-octylboronic acid, n-nonylboronic acid, n-decylboronic acid, n-undecanylboronic acid, n-dodecanylboronic acid, n-tridecanylboronic acid, n-tetradecanylboronic acid, n-pentadecanylboronic acid, n-hexadecanylboronic acid, n-heptadecanylboronic acid, n-octadecanylboronic acid, n-nonadecanylboronic acid, and n-icosanylboronic acid. Examples of compounds that can be converted to the exemplified boronic acids in the presence of water include salts of the boronic acids.

[0029] Specifically, the monoboronic acid represented by the above formula (I) is preferably ethylboronic acid, n-propylboronic acid, n-butylboronic acid, or n-pentylboronic acid, and more preferably n-propylboronic acid or n-butylboronic acid. In addition, examples of compounds that can be converted to these exemplified boronic acids in the presence of water include salts of the boronic acids.

[0030] The boron element content (b t ) must be 0.3 to 2.0 mass%. t If the content of (b) is less than 0.3% by mass, crosslinking by the boron-containing compound (B) becomes insufficient, and a polarizing film having high polarizing performance and high transmittance cannot be obtained. t ) is preferably 0.5 mass% or more. t If (b) exceeds 2.0 mass%, the reaction between the boron-containing compound (B) and PVA proceeds excessively, inhibiting the formation of the iodine-based dye, making it impossible to obtain a polarizing film with high polarizing performance and high transmittance. t The boron content (b) derived from the boron-containing compound (B) in the polarizing film is preferably 1.8% by mass or less, more preferably 1.6% by mass or less, even more preferably 1.4% by mass or less, particularly preferably 1.3% by mass or less, and most preferably 1.2% by mass or less. t )teeth, 1The boron content (b t As a sample for measuring the total boron element content (T) described below, a polarizing film that has been conditioned at 23° C. and 50% RH for 16 hours is used.

[0031] The total boron content (T) of the polarizing film must be 3.0 to 7.0% by mass. If the total boron content (T) in the polarizing film is less than 3.0% by mass, the number of crosslinking points becomes insufficient, causing the orientation of the PVA to become disordered, and a polarizing film with high polarization performance and high transmittance cannot be obtained. (T) is preferably 3.5% by mass or more, more preferably 4.1% by mass or more, and even more preferably 4.2% by mass or more. On the other hand, if the total boron content (T) in the polarizing film exceeds 7.0% by mass, the iodine-based dye is excessively adsorbed in the polarizing film, resulting in a decrease in polarization performance. In addition, the PVA film is more likely to break during the drying process and stretching process described below, resulting in a decrease in productivity of the polarizing film. The total boron content (T) in the polarizing film is preferably 6.5% by mass or less, more preferably 5.5% by mass or less, even more preferably 5.0% by mass or less, and particularly preferably 4.8% by mass or less. The total boron element content (T) in the polarizing film can be determined by ICP emission spectrometry, etc. Specifically, it can be obtained by the method described in the Examples.

[0032] The boron element content (b) derived from the boron-containing compound (B) relative to the total boron element content (T) (mass%) in the polarizing film t ) (mass%) ratio (b t / T) must be between 0.10 and 0.30. t When the ratio (b / T) is less than 0.10, the proportion of crosslinking points derived from the boron-containing compound (B) among all crosslinking points of the PVA in the polarizing film is too low, and the effect of improving the polarizing performance by the boron-containing compound (B) becomes insufficient. t / T) is preferably 0.12 or more, and more preferably 0.15 or more. tIf the ratio (b / T) exceeds 0.30, the proportion of crosslinking points derived from the boron-containing compound (B) among all crosslinking points of the PVA in the polarizing film is too high, which inhibits the formation of iodine-based dyes and may make it impossible to obtain a polarizing film with high polarizing performance and high transmittance. t / T) is preferably 0.27 or less, more preferably 0.25 or less, further preferably 0.23 or less, particularly preferably 0.18 or less.

[0033] Fig. 1 is a schematic diagram showing a cross section in the thickness direction of the polarizing film of the present invention. The polarizing film will be further described with reference to Fig. 1. The polarizing film has a total thickness t t 7.5% of the thickness of the surface part 2 and the thickness of the surface part 2 o and the total thickness of the polarizing film, t t "t o =t t The boron element concentration (b o ) must be 2.2 to 10.0 atomic percent. (b o If the content of (b) is less than 2.2 atomic %, the effect of the boron-containing compound (B) in suppressing the dissolution of boric acid from the polarizing film surface becomes insufficient, and the effect of improving the polarizing performance becomes small, so that a polarizing film with high polarizing performance and high transmittance cannot be obtained. o ) is preferably 2.4 atomic % or more, and more preferably 2.8 atomic % or more. o If the content of the boron-containing compound (B) exceeds 10.0 atomic %, there will be no problem with the polarizing performance, but the productivity of the polarizing film will decrease due to the formation of precipitates of the boron-containing compound (B) on the surface of the polarizing film. o The boron element concentration (b) derived from the boron-containing compound (B) in the surface portion 2 on both sides of the polarizing film is preferably 8 atomic % or less, more preferably 6 atomic % or less, further preferably 5 atomic % or less, and particularly preferably 4 atomic % or less. o ) is preferably in the above range.

[0034] Boron element concentration (b o) can be determined using an X-ray photoelectron spectrometer equipped with a gas cluster ion beam gun (GCIB XPS). By repeating etching and measurement using GCIB XPS, the boron element concentration derived from the boron-containing compound (B) is measured at regular intervals from the surface of the polarizing film to the inside. Then, the average value of the boron element concentration derived from the boron-containing compound (B) in the above range (surface portion 2) is taken as the boron element concentration (b o Specifically, it can be determined by the method described in the Examples below. i ), (c o ), and (c i ) and (b o ) can be calculated in the same manner.

[0035] From the center 3 of the polarizing film to the outside, a total thickness t t 7.5% range (center 4, thickness t i and the total thickness of the polarizing film, t t "t i =t t The boron element concentration (b i ) is preferably 0.5 to 2.0 atomic %. In addition, the boron element concentration (c i It is also preferable that (b) is 3.5 to 8.0 atomic %. i ) is 0.5 to 2.0 atomic %, and (c i ) is more preferably 3.5 to 8.0 atomic %.

[0036] The boron element concentration (b i If the content of (b) exceeds 2.0 atomic %, the amount of the boron-containing compound (B) present inside the polarizing film will be excessive, which may inhibit the formation of the iodine-based dye, which is not preferable. i ) is more preferably 1.8 atomic % or less, further preferably 1.5 atomic % or less, and particularly preferably 1.3 atomic % or less. iIf the content of the boron-containing compound (B) is less than 0.5 atomic %, the amount of the boron-containing compound (B) inside the polarizing film may be insufficient, resulting in insufficient improvement in the polarizing performance. i ) is more preferably 0.8 atomic % or more, and further preferably 0.9 atomic % or more.

[0037] The boron element concentration (c i If the content of (c) exceeds 8.0 atomic %, it is not preferable because the adsorption of the boron-containing compound (B) into the polarizing film is inhibited. i ) is more preferably 7.0 atomic % or less, and even more preferably 6.0 atomic % or less. i If the ratio of (c) is less than 3.5 atomic %, the number of crosslinking points will be insufficient, and the PVA may not be maintained in an oriented state, resulting in a risk of not being able to obtain a polarizing film with high polarizing performance. i ) is more preferably 4.0 atomic % or more, further preferably 4.5 atomic % or more, and particularly preferably 5.0 atomic % or more.

[0038] The boron element concentration (c i ) relative to the boron concentration (b i ) ratio (b i / c i It is preferable that the ratio (b i / c i If the ratio (b) is less than 0.01, the ratio of the boron-containing compound (B) to the boric acid (C) inside the polarizing film is low, and the effect of improving the polarization performance by adding the boron-containing compound (B) may be insufficient. i / c i ) is more preferably 0.08 or more, even more preferably 0.10 or more, particularly preferably 0.12 or more, and most preferably 0.15 or more. i / c i If the ratio (b) exceeds 0.25, the formation of iodine-based pigments is inhibited, which is undesirable. i / c i ) is more preferably 0.20 or less.

[0039] The polarizing film is formed from at least one surface 1 to the inside, with a total thickness t t The concentration of boron element (c o ) is preferably 3.3 to 7.8 atomic %. o When the content of boric acid in the polarizing film is less than 3.3 atomic %, boric acid is often excessively dissolved from the polarizing film. When boric acid is excessively dissolved, a polarizing film with high polarizing performance may not be obtained. o ) is more preferably 4.0 atomic % or more, and even more preferably 4.5 atomic % or more. o If the content of (c) exceeds 7.8 atomic %, the surface 1 of the polarizing film may be easily scratched, or the adsorption of the boron-containing compound (B) to the PVA film may be inhibited. o The boron element concentration (c) derived from boric acid (C) in the surface portion 2 on both sides of the polarizing film is more preferably 7.0 atomic % or less, further preferably 6.5 atomic % or less, particularly preferably 5.5 atomic % or less, and most preferably 4.8 atomic % or less. o ) is more preferably in the above range.

[0040] The polarizing film is formed from at least one surface 1 to the inside, with a total thickness t t The boron element concentration (b o ) from the center 3 of the polarizing film to the outside, the total thickness t t The concentration of boron (b i ) is preferable. i ) for (b o ) ratio (b o / b iIf (b) is less than 1, the effect of the boron-containing compound (B) in suppressing the elution of boric acid on the surface of the polarizing film becomes insufficient, resulting in a small improvement in polarizing performance, and therefore a polarizing film with high polarizing performance and high transmittance may not be obtained, or the boron-containing compound (B) present inside the polarizing film may become excessive, inhibiting the formation of iodine-based dyes. i ) for (b o ) ratio (b o / b i ) is more preferably 1.1 or more, even more preferably 1.5 or more, particularly preferably 2.0 or more, and most preferably 2.5 or more. o / b i ) is preferably 8.0 or less, more preferably 7.0 or less. In terms of obtaining a polarizing film with extremely high polarizing performance and transmittance and further improving the productivity of the polarizing film, the ratio (b o / b i The boron element concentration (b o ) is the boron element concentration (b i ) is more preferable.

[0041] The polarizing film is formed from at least one surface 1 to the inside, with a total thickness t t The concentration of boron element (c o ) from the center of the polarizing film to the outside, the total thickness t t The concentration of boron element derived from boric acid (C) in the range of up to 7.5% (center 4) i ) is preferable. i ) for (c o ) ratio (c o / c iIf (c) is 1 or more, the surface 1 of the polarizing film may be easily scratched, the adsorption of the boron-containing compound (B) to the PVA film may be hindered, or the number of crosslinking points may be insufficient, preventing the PVA from maintaining an oriented state, making it difficult to obtain a polarizing film with high polarizing performance. i ) for (c o ) ratio (c o / c i ) is more preferably 0.99 or less, even more preferably 0.95 or less, particularly preferably 0.90 or less, and most preferably 0.85 or less. On the other hand, in order to obtain a polarizing film with higher polarizing performance and to facilitate the adsorption of the boron-containing compound (B) into the inside of the polarizing film, the ratio (c o / c i The boron element concentration (c o ) is the concentration of boron element (c i ) is more preferably lower.

[0042] The thickness of the polarizing film is preferably 5 to 60 μm. If the thickness is less than 5 μm, stretching breakage may easily occur during production, and the productivity may decrease. The thickness is more preferably 10 μm or more. On the other hand, if the thickness exceeds 60 μm, the performance required for a polarizing plate, such as thinness and weight reduction, may not be satisfied. For this reason, the thickness is more preferably 45 μm or less, further preferably 30 μm or less, and particularly preferably 25 μm or less.

[0043] <PVA(A)> The PVA (A) in the present invention is a polymer having a vinyl alcohol unit (-CH2-CH(OH)-) as a main structural unit.

[0044] The degree of polymerization of the PVA (A) contained in the polarizing film of the present invention is preferably within the range of 1,500 to 6,000, more preferably within the range of 1,800 to 5,000, and even more preferably within the range of 2,000 to 4,000. When the degree of polymerization is 1,500 or more, the durability of the polarizing film obtained by uniaxially stretching the film can be improved. On the other hand, when the degree of polymerization is 6,000 or less, an increase in production costs and poor processability during film formation can be suppressed. In this specification, the degree of polymerization of the PVA (A) means the average degree of polymerization measured in accordance with the description of JIS K6726-1994.

[0045] The saponification degree of the PVA (A) contained in the polarizing film of the present invention is preferably 95 mol% or more, more preferably 96 mol% or more, and even more preferably 98 mol% or more, from the viewpoint of the water resistance of the polarizing film obtained by uniaxially stretching the film. In this specification, the saponification degree of the PVA refers to the ratio (mol%) of the number of moles of the vinyl alcohol unit to the total number of moles of the structural unit (typically a vinyl ester unit) that can be converted to a vinyl alcohol unit (-CH2-CH(OH)-) by saponification that the PVA has. The saponification degree can be measured according to the description of JIS K6726-1994.

[0046] The method for producing the PVA (A) used in the present invention is not particularly limited. For example, a method of converting vinyl ester units of polyvinyl ester obtained by polymerizing vinyl ester monomers into vinyl alcohol units can be mentioned. The vinyl ester monomer used for producing the PVA (A) is not particularly limited, but examples thereof include vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, and vinyl benzoate. From an economical viewpoint, vinyl acetate is preferred.

[0047] The PVA (A) used in the present invention may be a vinyl ester copolymer obtained by copolymerizing a vinyl ester monomer with another monomer copolymerizable therewith, in which the vinyl ester units are converted into vinyl alcohol units. Examples of other monomers copolymerizable with the vinyl ester monomer include α-olefins having 2 to 30 carbon atoms, such as ethylene, propylene, 1-butene, and isobutene; (meth)acrylic acid or a salt thereof; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate; (meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, diacetone(meth)acrylamide, (meth)acrylamidopropanesulfonic acid or a salt thereof, and (meth)acrylamidopropyldimethylamine or a salt thereof. salts thereof, (meth)acrylamide derivatives such as N-methylol (meth)acrylamide or its derivatives; N-vinylamides such as N-vinylformamide, N-vinylacetamide, and N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, and stearyl vinyl ether; vinyl cyanides such as (meth)acrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or its salts, esters, or acid anhydrides; itaconic acid or its salts, esters, or acid anhydrides; vinyl silyl compounds such as vinyltrimethoxysilane; and unsaturated sulfonic acids. The vinyl ester copolymers described above may have structural units derived from one or more of the other monomers described above.The other monomers can be used by having them present in the reaction vessel beforehand when the vinyl ester monomer is subjected to the polymerization reaction, or by adding them to the reaction vessel during the progress of the polymerization reaction, etc. From the viewpoint of optical performance, the content of units derived from other monomers is preferably 10 mol % or less, more preferably 5 mol % or less, and even more preferably 2 mol % or less, based on the number of moles of all structural units constituting PVA (A).

[0048] Ethylene is preferred as the monomer copolymerizable with the vinyl ester monomer, since it improves the stretchability, allows stretching at a higher temperature, reduces the occurrence of problems such as breakage during stretching, and further improves the productivity of the polarizing film. When PVA (A) contains ethylene units, the content of the ethylene units is preferably 1 to 10 mol%, more preferably 2 to 6 mol%, based on the number of moles of all structural units constituting PVA (A), from the viewpoints of the stretchability and stretchable temperature as described above.

[0049] The PVA film used in the production of the polarizing film of the present invention may contain a plasticizer in addition to the above-mentioned PVA (A). Preferred plasticizers include polyhydric alcohols, and specific examples thereof include ethylene glycol, glycerin, propylene glycol, diethylene glycol, diglycerin, triethylene glycol, tetraethylene glycol, and trimethylolpropane. Furthermore, one or more of these plasticizers may be contained. Among these, glycerin is preferred from the viewpoint of improving the stretchability.

[0050] The content of the plasticizer in the PVA film used in the production of the polarizing film of the present invention is preferably within the range of 1 to 20 parts by mass, more preferably within the range of 3 to 17 parts by mass, and even more preferably within the range of 5 to 15 parts by mass, relative to 100 parts by mass of PVA (A). When the content is 1 part by mass or more, the stretchability of the film is improved. On the other hand, when the content is 20 parts by mass or less, it is possible to prevent the film from becoming too flexible and the handling properties from being deteriorated.

[0051] The PVA film used in the production of the polarizing film of the present invention may further contain additives other than PVA (A) and plasticizers, such as fillers, processing stabilizers such as copper compounds, weathering stabilizers, colorants, UV absorbers, light stabilizers, antioxidants, antistatic agents, flame retardants, other thermoplastic resins, lubricants, fragrances, antifoaming agents, deodorants, extenders, peeling agents, release agents, reinforcing agents, crosslinking agents, fungicides, preservatives, and crystallization rate retarders, as necessary. The content of other additives in the PVA film is usually 10% by mass or less, and preferably 5% by mass or less.

[0052] The swelling degree of the PVA film used in the production of the polarizing film of the present invention is preferably within the range of 160 to 240%, more preferably within the range of 170 to 230%, and particularly preferably within the range of 180 to 220%. When the swelling degree is 160% or more, it is possible to suppress the crystallization from proceeding excessively, and it is possible to stably stretch the film to a high ratio. On the other hand, when the swelling degree is 240% or less, dissolution during stretching is suppressed, and it is possible to stretch the film even under higher temperature conditions.

[0053] <Method of manufacturing polarizing film> The thickness of the PVA film used in the manufacture of the polarizing film of the present invention is not particularly limited, but is generally 1 to 100 μm, preferably 5 to 60 μm, and particularly preferably 10 to 45 μm. If the PVA film is too thin, it tends to be easily cut during uniaxial stretching to manufacture the polarizing film. If the PVA film is too thick, it tends to be easily unevenly stretched during uniaxial stretching to manufacture the polarizing film, and the resulting polarizing film tends to be thick, making it difficult to use it in thin and small devices such as smartphones and notebook computers.

[0054] The width of the PVA film used in the manufacture of the polarizing film of the present invention is not particularly limited and can be determined depending on the application of the polarizing film to be manufactured. In recent years, the screen size of liquid crystal televisions and liquid crystal monitors has been increasing, so that the width of the PVA film used in the manufacture of the polarizing film is 3 m or more, which is suitable for these applications. On the other hand, if the width of the PVA film used in the manufacture of the polarizing film is too large, it is likely to be difficult to uniformly perform uniaxial stretching when the polarizing film is manufactured using a practical device, so the width of the PVA film used in the manufacture of the polarizing film is preferably 10 m or less.

[0055] The method for producing the PVA film used in the production of the polarizing film of the present invention is not particularly limited, and a production method that makes the thickness and width of the film uniform after film production is preferably adopted. For example, the polarizing film can be produced using a film-forming stock solution in which PVA (A) and, if necessary, one or more of the plasticizer, the other additives, and the surfactant described below are dissolved in a liquid medium, or a film-forming stock solution in which PVA (A) and, if necessary, one or more of the plasticizer, other additives, surfactant, and liquid medium are contained and PVA (A) is melted. When the film-forming stock solution contains at least one of the plasticizer, other additives, and surfactant, it is preferable that these components are uniformly mixed.

[0056] Examples of the liquid medium used to prepare the film-forming solution include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, glycerin, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, ethylenediamine, diethylenetriamine, etc., and one or more of these may be used. Among these, water is preferred from the viewpoints of environmental load and recovery.

[0057] The volatile fraction of the film-forming solution (the content ratio of volatile components such as liquid medium removed by volatilization or evaporation during film formation in the film-forming solution) varies depending on the film-forming method and film-forming conditions, but is generally preferably in the range of 50 to 95% by mass, more preferably in the range of 55 to 90% by mass. When the volatile fraction of the film-forming solution is 50% by mass or more, the viscosity of the film-forming solution does not become too high, filtration and degassing during preparation of the film-forming solution are smoothly performed, and a film with few foreign matter and defects is easily produced. On the other hand, when the volatile fraction of the film-forming solution is 95% by mass or less, the concentration of the film-forming solution does not become too low, and industrial film production is easy.

[0058] The film-forming solution preferably contains a surfactant. By containing a surfactant, the film-forming property is improved, the occurrence of unevenness in the thickness of the film is suppressed, and the film is easily peeled off from the metal roll or belt used in film formation. When a PVA film is produced from a film-forming solution containing a surfactant, the film may contain a surfactant. The type of the surfactant is not particularly limited, but an anionic surfactant or a nonionic surfactant is preferable from the viewpoint of peelability from the metal roll or belt.

[0059] Suitable anionic surfactants include, for example, carboxylic acid types such as potassium laurate; sulfate ester types such as polyoxyethylene lauryl ether sulfate, sodium alkyl sulfate, potassium alkyl sulfate, ammonium alkyl sulfate, triethanolamine alkyl sulfate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxypropylene alkyl ether sulfate, sodium polyoxyethylene alkyl phenyl ether sulfate, and octyl sulfate; sulfonic acid types such as sodium alkyl sulfonate, potassium alkyl sulfonate, ammonium alkyl sulfonate, triethanolamine alkyl sulfonate, sodium alkyl benzene sulfonate, disodium dodecyl diphenyl ether disulfonate, sodium alkyl naphthalene sulfonate, disodium alkyl sulfosuccinate, disodium polyoxyethylene alkyl sulfosuccinate, and dodecyl benzene sulfonate; and phosphate ester types such as sodium alkyl phosphate, potassium alkyl phosphate, ammonium alkyl phosphate, triethanolamine alkyl phosphate, sodium polyoxyethylene alkyl ether phosphate, sodium polyoxypropylene alkyl ether phosphate, and sodium polyoxyethylene alkyl phenyl ether phosphate.

[0060] Suitable examples of nonionic surfactants include alkyl ether types such as polyoxyethylene oleyl ether; alkyl phenyl ether types such as polyoxyethylene octylphenyl ether; alkyl ester types such as polyoxyethylene laurate; alkyl amine types such as polyoxyethylene lauryl amino ether; alkyl amide types such as polyoxyethylene lauric acid amide; polypropylene glycol ether types such as polyoxyethylene polyoxypropylene ether; alkanolamide types such as lauric acid diethanolamide and oleic acid diethanolamide; and allyl phenyl ether types such as polyoxyalkylene allyl phenyl ether.

[0061] These surfactants can be used alone or in combination of two or more.

[0062] When the film-forming solution contains a surfactant, the content is preferably within the range of 0.01 to 0.5 parts by mass, more preferably within the range of 0.02 to 0.3 parts by mass, and particularly preferably within the range of 0.05 to 0.2 parts by mass, relative to 100 parts by mass of PVA (A) contained in the film-forming solution. When the content is 0.01 parts by mass or more, the film-forming property and the peeling property are further improved. On the other hand, when the content is 0.5 parts by mass or less, it is possible to suppress the surfactant from bleeding out onto the surface of the PVA film, causing blocking and reducing the handleability.

[0063] Examples of the film-forming method when forming a PVA film using the film-forming solution include a cast film-forming method, an extrusion film-forming method, a wet film-forming method, and a gel film-forming method. These film-forming methods may be used alone or in combination of two or more. Among these film-forming methods, the cast film-forming method and the extrusion film-forming method are preferred because they can produce a PVA film that is uniform in thickness and width and has good physical properties and is used to manufacture a polarizing film. The formed PVA film can be dried or heat-treated as necessary.

[0064] As a specific example of a method for producing the PVA film used in the production of the polarizing film of the present invention, for example, a method is preferably adopted industrially in which the above film-forming solution is uniformly discharged or cast onto the peripheral surface of a rotating heated first roll (or belt) located at the most upstream side using a T-shaped slit die, a hopper plate, an I-die, a lip coater die, etc., volatile components are evaporated from one side of the film discharged or cast onto the peripheral surface of the first roll (or belt) to dry it, and then the film is further dried on the peripheral surface of one or more rotating heated rolls arranged downstream, or further dried by passing through a hot air dryer, and then wound up by a winding device. Drying by a heated roll and drying by a hot air dryer may be carried out in appropriate combination. A multi-layer PVA film may also be produced by forming a layer made of PVA (A) on one side of a substrate film composed of a single resin layer.

[0065] The method for producing the polarizing film of the present invention is not particularly limited. A suitable production method is a method for producing a polarizing film including a dyeing process for dyeing a PVA film with a dichroic dye and a stretching process for uniaxially stretching the film, in which the film is immersed in an aqueous solution containing a boric acid crosslinking agent and then immersed in an aqueous solution containing a boron-containing compound (B). In addition to the dyeing process and stretching process, the PVA film may be further subjected to a swelling process, a boric acid crosslinking process, a fixing process, a washing process, a drying process, a heat treatment, etc., as necessary. The order of each process is not particularly limited, and one or more of the processes may be performed simultaneously. Also, one or more of the processes may be performed twice or more.

[0066] The swelling treatment can be carried out by immersing the PVA film in water. The temperature of the water in which the film is immersed is preferably within the range of 20 to 40°C, more preferably within the range of 22 to 38°C, and even more preferably within the range of 25 to 35°C. The time for immersion in water is, for example, preferably within the range of 0.1 to 5 minutes, and more preferably within the range of 0.2 to 3 minutes. The water in which the film is immersed is not limited to pure water, and may be an aqueous solution in which various components are dissolved, or a mixture of water and a hydrophilic medium.

[0067] The dyeing treatment can be carried out by contacting the PVA film with a dichroic dye. As the dichroic dye, an iodine-based dye or a dichroic dye is generally used. The dyeing treatment may be carried out at any stage before, during, or after the stretching treatment. The dyeing treatment is generally carried out by immersing the PVA film in a solution (particularly an aqueous solution) containing iodine-potassium iodide as a dye bath, or a solution (particularly an aqueous solution) containing a plurality of dichroic dyes. The concentration of iodine in the dye bath is preferably within a range of 0.01 to 0.5% by mass, and the concentration of potassium iodide is preferably within a range of 0.01 to 10% by mass. The temperature of the dye bath is preferably 20 to 50°C, particularly 25 to 40°C. The suitable dyeing time is 0.2 to 5 minutes. When a dichroic dye is used, the dichroic dye is preferably an aqueous dye. The dye concentration in the dye bath is preferably 0.001 to 10% by mass. Also, dyeing assistants may be used as necessary, and inorganic salts such as sodium sulfate, surfactants, etc. may be used. When sodium sulfate is used, 0.1 to 10 mass % is preferable. The dyeing temperature is preferably 30 to 80°C. Specific dichroic dyes include CI Direct Yellow 28, CI Direct Orange 39, CI Direct Yellow 12, CI Direct Yellow 44, CI Direct Orange 26, CI Direct Orange 71, CI Direct Orange 107, CI Direct Red 2, CI Direct Red 31, CI Direct Red 79, CI Direct Red 81, CI Direct Red 247, CI Direct Green 80, and CI Direct Green 59, and dichroic dyes developed for polarizing plate manufacturing are preferable.

[0068] The boric acid crosslinking treatment can be performed by immersing the PVA film in an aqueous solution containing a boric acid crosslinking agent. By subjecting the PVA film to a boric acid crosslinking treatment, the PVA molecular chains are crosslinked, improving the orientation of the PVA molecular chains. As a result, the orientation of the dichroic dye adsorbed to the PVA film is improved, and the optical performance of the resulting polarizing film is improved. From this viewpoint, it is more preferable to perform the boric acid crosslinking treatment after the dyeing treatment and before the stretching treatment. As the boric acid crosslinking agent, one or more of boron-containing inorganic compounds such as boric acid and borax and other borate salts can be used, and from the viewpoint of ease of handling, the boric acid crosslinking agent is preferably boric acid. From the viewpoint of maintaining sufficient stretchability, the concentration of the boric acid crosslinking agent in the aqueous solution containing the boric acid crosslinking agent is preferably 1 to 10 mass%, more preferably 2 to 7 mass%. If the concentration of the boric acid crosslinking agent exceeds 10 mass%, crosslinking may proceed excessively, resulting in a decrease in stretchability. In addition, when the concentration of the boric acid crosslinker is less than 1% by mass, the orientation of the dichroic dye adsorbed on the PVA film may not be sufficiently improved, and the polarization performance of the resulting polarizing film may not be sufficiently improved. The aqueous solution containing the boric acid crosslinker may contain an auxiliary such as potassium iodide. The concentration of the boron-containing compound (B) in the aqueous solution containing the boric acid crosslinker is preferably 2.0% by mass or less, more preferably 0.5% by mass or less, and even more preferably 0.1% by mass, and it is particularly preferable that the aqueous solution does not substantially contain the boron-containing compound (B). In addition, the ratio of the concentration (mass%) of the boron-containing compound (B) to the concentration (mass%) of the boric acid crosslinker in the aqueous solution containing the boric acid crosslinker [boron-containing compound (B) / boric acid crosslinker] is preferably less than 1, more preferably 0.5 or less, even more preferably 0.25 or less, and particularly preferably 0.1 or less. In order to efficiently perform boric acid crosslinking, the temperature of the aqueous solution containing the boric acid crosslinking agent is preferably 20 to 50°C, and particularly preferably 25 to 40°C.

[0069] In the manufacturing method of the present invention, the PVA film may be immersed in an aqueous solution containing a boric acid crosslinking agent in any of the treatments, but is preferably immersed in the boric acid crosslinking treatment. Also, the PVA film may be immersed in an aqueous solution containing a boric acid crosslinking agent in a plurality of treatments.

[0070] Apart from the stretching treatment described later, the PVA film may be stretched (pre-stretched) during or between each of the above-mentioned treatments. In this way, the total stretching ratio (a ratio obtained by multiplying the stretching ratios in each treatment) of the pre-stretching performed before the stretching treatment is preferably 1.5 times or more, more preferably 2.0 times or more, and even more preferably 2.5 times or more, based on the original length of the raw material PVA film before stretching, from the viewpoint of the optical performance of the resulting polarizing film. On the other hand, the total stretching ratio is preferably 4.0 times or less, and more preferably 3.5 times or less. The stretching ratio in the swelling treatment is preferably 1.05 to 2.5 times. The stretching ratio in the dyeing treatment is preferably 1.1 to 2.5 times. The stretching ratio in the boron crosslinking treatment is preferably 1.1 to 2.5 times.

[0071] The stretching treatment may be performed by either a wet stretching method or a dry stretching method. In the case of the wet stretching method, the stretching is performed in an aqueous solution. The stretching can also be performed in the above-mentioned dye bath or in an aqueous solution of boric acid. In the case of the dry stretching method, the stretching may be performed at room temperature, or while heating, or the stretching can be performed in air using the PVA film after absorbing water. Among these, the wet stretching method is preferred, and it is more preferred to perform the stretching treatment in an aqueous solution containing boric acid. The concentration of boric acid in the aqueous solution of boric acid is preferably within the range of 0.5 to 6% by mass, more preferably within the range of 1 to 5% by mass. The aqueous solution of boric acid may also contain potassium iodide, and the concentration is preferably within the range of 0.01 to 10% by mass. The stretching temperature in the stretching treatment is preferably 30°C or higher, more preferably 40°C or higher, and even more preferably 50°C or higher. On the other hand, the stretching temperature is preferably 90°C or lower, more preferably 80°C or lower, and even more preferably 70°C or lower. The stretching ratio in the stretching process is preferably 2.0 to 4.0 times. From the viewpoint of the optical properties of the resulting polarized film, the stretching ratio is more preferably 2.2 times or more. Meanwhile, the stretching ratio is more preferably 3.5 times or less. From the viewpoint of the optical properties of the resulting polarized film, the total stretching ratio before the fixing process described later is preferably 5 times or more, more preferably 5.5 times or more, based on the original length of the raw material PVA film before stretching. There is no particular upper limit to the stretching ratio, but the stretching ratio is preferably 8 times or less.

[0072] There is no particular restriction on the direction of uniaxial stretching when a long PVA film is stretched, and uniaxial stretching in the long direction, uniaxial stretching in the transverse direction, or so-called oblique stretching can be adopted, but uniaxial stretching in the long direction is preferred because it produces a polarizing film with excellent optical performance. Uniaxial stretching in the long direction can be performed by using a stretching device equipped with multiple rolls parallel to each other and changing the peripheral speed between the rolls. On the other hand, uniaxial stretching in the transverse direction can be performed using a tenter-type stretching machine.

[0073] In the production of a polarizing film, it is preferable to carry out a fixing treatment after the stretching treatment in order to strengthen the adsorption of the dichroic dye (such as an iodine-based dye) to the PVA film. As the fixing treatment bath used for the fixing treatment, an aqueous solution containing a boron-containing compound (B) is preferably used. In addition, boric acid, an iodine compound, a metal compound, etc. may be further added to the fixing treatment bath as necessary. The temperature of the fixing treatment bath is preferably 35°C to 80°C. On the other hand, if the temperature of the fixing treatment bath exceeds 80°C, the polarizing film may dissolve in the fixing treatment bath or the polarizing film may wrinkle, resulting in a decrease in the polarization performance. The temperature is more preferably 75°C or less, and even more preferably 70°C or less. The stretching ratio in the fixing treatment is preferably 1.3 times or less, more preferably 1.2 times or less, and even more preferably less than 1.1 times.

[0074] The boron-containing compound (B) may be adsorbed onto the PVA film in any of the dyeing, stretching, and fixing processes after the PVA film is immersed in an aqueous solution containing a boric acid crosslinking agent. In order to efficiently remove unnecessary iodine-based dyes and to suppress cutting of the PVA film during stretching, it is preferable to adsorb the boron-containing compound (B) onto the PVA film in the fixing process after stretching. The boron-containing compound (B) may be used alone or in combination of two or more. In order to allow the substitution reaction between the boron-containing compound (B) and boric acid (C) to proceed quickly on the surface of the PVA film, the concentration of the boron-containing compound (B) in the aqueous solution used for adsorption of the boron-containing compound (B) must be 1.5 to 5.0% by mass. If the concentration is lower than 1.5% by mass, the adsorption of the boron-containing compound (B) onto the surface of the PVA film is delayed. The concentration is preferably 2.0% by mass or more, more preferably 2.5% by mass or more. On the other hand, if the concentration is higher than 5.0% by mass, the boron-containing compound (B) is excessively adsorbed on the surface of the PVA film, and the substitution reaction between the boron-containing compound (B) and boric acid (C) is difficult to proceed. In addition, the boron-containing compound (B) may precipitate on the surface of the obtained polarizing film, resulting in a deterioration in optical performance. For this reason, the concentration of the boron-containing compound (B) is preferably 4.5% by mass or less, more preferably 4.0% by mass or less. The concentration of the boric acid crosslinking agent in the aqueous solution containing the boron-containing compound (B) is preferably 1.5% by mass or less, more preferably 1.0% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less, and it is most preferable that the aqueous solution does not substantially contain the boric acid crosslinking agent. In addition, in the aqueous solution containing the boron-containing compound (B), the ratio of the concentration (mass%) of the boric acid crosslinker to the concentration (mass%) of the boron-containing compound (B) [boric acid crosslinker / boron-containing compound (B)] is preferably less than 1, more preferably 0.5 or less, even more preferably 0.25 or less, and particularly preferably 0.1 or less.

[0075] From the viewpoint of improving optical performance, the aqueous solution containing the boron-containing compound (B) preferably contains an iodide auxiliary such as potassium iodide, and the concentration of the iodide is preferably 0.5 to 15 mass%. The temperature of the aqueous solution containing the boron-containing compound (B) is also preferably 35 to 80°C. If the temperature is less than 35°C, the rate of substitution of the boron-containing compound (B) with the boric acid (C) may be slow, and the effect of improving the polarization performance may be insufficient. The temperature is more preferably 40°C or higher, and even more preferably 45°C or higher. On the other hand, if the temperature is too high, the PVA film may dissolve in the aqueous solution, or the obtained polarizing film may wrinkle, resulting in a decrease in polarization performance. For this reason, the temperature is more preferably 75°C or lower, and even more preferably 70°C or lower. The time for immersing the PVA film in the aqueous solution is preferably 5 to 400 seconds. The time is more preferably 10 seconds or more, even more preferably 15 seconds or more, and particularly preferably 20 seconds or more. On the other hand, the time is more preferably 350 seconds or less, further preferably 250 seconds or less, particularly preferably 150 seconds or less, and most preferably 70 seconds or less.

[0076] Methods for adsorbing the boron-containing compound (B) onto the PVA film include (1) immersing the PVA film alone in an aqueous solution containing the boron-containing compound (B) without laminating it to a substrate film or the like, (2) laminating a substrate film to one side of the PVA film so as to reduce the occurrence of wrinkles during the fixing process, and then immersing the resulting laminate in the aqueous solution, (3) spraying an aqueous solution containing the boron-containing compound (B) onto the polarizing film surface, and (4) applying the aqueous solution onto the PVA film surface using a roll coated with the aqueous solution, among which (1) is preferred. According to method (1), adsorption of the boron-containing compound (B) from the surface to the center of the PVA film proceeds equally on both sides, and is therefore preferred.

[0077] As a method for producing the polarizing film of the present invention by adsorbing the boron-containing compound (B) to the PVA film in the fixing treatment, a method of performing a swelling treatment, a stretching treatment, and a fixing treatment in this order, and a method of performing a swelling treatment, a boric acid crosslinking treatment, a stretching treatment, and a fixing treatment in this order are preferred, with the latter being more preferred. After performing these treatments, at least one treatment selected from the group consisting of a washing treatment, a drying treatment, and a heat treatment may be further performed as necessary. After the boron-containing compound (B) is adsorbed to the PVA film, it is preferred not to immerse the PVA film in an aqueous solution containing a boric acid crosslinking agent.

[0078] The washing treatment is generally performed by immersing the film in distilled water, pure water, an aqueous solution, or the like. In this case, from the viewpoint of improving optical performance, it is preferable to use an aqueous solution containing an iodide such as potassium iodide as an auxiliary, and the concentration of the iodide is preferably 0.5 to 10 mass %. The temperature of the aqueous solution in the washing treatment is generally 5 to 50°C, preferably 10 to 45°C, and more preferably 15 to 40°C. From the economic viewpoint, it is not preferable that the temperature of the aqueous solution is too low, and if the temperature of the aqueous solution is too high, the optical performance may be reduced.

[0079] The conditions for the drying treatment are not particularly limited, but drying is preferably carried out at a temperature within the range of 30 to 150° C., particularly within the range of 50 to 130° C. Drying at a temperature within this range tends to produce a polarizing film with excellent dimensional stability.

[0080] By carrying out a heat treatment after the drying treatment, a polarizing film with even better dimensional stability can be obtained. Here, the heat treatment refers to a treatment in which a polarizing film with a moisture content of 5% or less after the drying treatment is further heated to improve the dimensional stability of the polarizing film. The conditions for the heat treatment are not particularly limited, but it is preferable to carry out the heat treatment within the range of 60°C to 150°C, particularly within the range of 70°C to 150°C. If the heat treatment is carried out at a temperature lower than 60°C, the dimensional stabilization effect of the heat treatment is insufficient, and if the heat treatment is carried out at a temperature higher than 150°C, the polarizing film may be significantly discolored red.

[0081] The polarizing film of the present invention thus obtained preferably has a transmittance of 42.0% or more and a polarization degree of 99.85% or more. If the transmittance of the polarizing film is less than 42.0%, the brightness of the resulting LCD may be insufficient. The transmittance is more preferably 43.0% or more, and even more preferably 43.5% or more. Meanwhile, the transmittance is usually 48% or less. Furthermore, if the polarization degree of the polarizing film is 99.85% or more, an LCD panel with high image quality can be obtained. The polarization degree is more preferably 99.9% or more. The transmittance and polarization degree of the polarizing film are measured by the methods described in the examples below.

[0082] The polarizing film of the present invention is usually used as a polarizing plate by laminating an optically transparent and mechanically strong protective film on either or both sides of the film. Examples of the protective film include cellulose triacetate (TAC) film, cellulose acetate butyrate (CAB) film, acrylic film, and polyester film. Examples of adhesives for lamination include PVA adhesives and UV-curable adhesives.

[0083] The polarizing plate obtained as described above may be laminated with a retardation film, a viewing angle improving film, a brightness improving film, etc. In addition, the polarizing plate may be coated with an acrylic or other adhesive, and then laminated with a glass substrate to be used as a part of an LCD. EXAMPLES

[0084] The present invention will be described in detail with reference to the following examples, but the present invention is not limited to these examples. The evaluation methods used in the following examples and comparative examples are shown below.

[0085] <Calculation of total boron element content (T) in polarizing film> The mass [A(g)] of the polarizing film after 16 hours of humidity conditioning at 23°C and 50% RH was measured, and the polarizing film was dissolved in 20 mL of distilled water so that the polarizing film was 0.005% by mass. The aqueous solution in which the polarizing film was dissolved was used as a measurement sample, and its mass [B(g)] was measured. The boron concentration [C(ppm)], potassium concentration [D(ppm)], and iodine concentration [E(ppm)] of the measurement sample were measured using a Shimadzu Corporation multi-type ICP emission spectrometer (ICP). The measured values ​​were then substituted into the following formulas (1), (2), and (3) to calculate the total boron element content (mass%), total potassium element content (mass%), and total iodine element content (mass%) in the polarizing film. Total boron content in polarizing film (T, mass%) =[(C×10 -6 ×B) / A]×100 (1) Total potassium content in polarizing film (F, mass%) =[(D×10 -6 ×B) / A]×100 (2) Total iodine content in polarizing film (G, mass%) =[(E×10 -6 ×B) / A]×100 (3)

[0086] <Calculation of moisture content (H, mass%) in polarizing film> Approximately 0.1 g of the polarized film was cut out after conditioning at 23°C and 50% RH for 16 hours, and its mass [X(g)] was measured. The polarized film was dried in a dryer at 105°C for 16 hours, and then its mass [Y(g)] was measured. The obtained value was substituted into the following formula (4) to calculate the moisture content in the polarized film. Moisture content in polarizing film (H, mass%) =(XY) / X × 100 (4)

[0087] <Content of boron element derived from boron-containing compound (B) in polarizing film (b t ) Measurement> The polarizing film was dissolved in heavy water to a concentration of 0.003% by mass, and the solution was concentrated in a rotary evaporator to a concentration of 0.15% by mass. 1 The sample was used for H-NMR measurement. 1 H-NMR (JNM-AL400: 400 MHz, manufactured by JEOL Ltd.) was performed at 80° C., and the number of accumulations was set to 256. Analysis was performed using ALICE2 (manufactured by JEOL Ltd.) in the following manner. 1For the H-NMR chart, the phase was adjusted so that the baseline was smooth, and the average point was set to 20 to automatically correct the baseline. Next, the peak of heavy water, the measurement solvent, was automatically set as the reference so that it was at 4.65 ppm. After that, the hydrogen peak of the hydrocarbon group contained in the boron-containing compound (B) was integrated as shown in Figure 2 to obtain its peak area (area I). ​​At this time, the sum of the hydrogen peak areas of the hydrocarbon groups contained in the boron-containing compound (B) that do not overlap with the hydrogen peak derived from PVA (area J) was used as the standard for the peak area, and the number of hydrogen atoms in the corresponding hydrocarbon group of the boron-containing compound (B) was set to be the same as the value of area J. Next, the hydrogen peaks in the range of 1.6 to 2.4 ppm were considered to be the sum of the hydrogen peaks derived from the methylene groups of PVA and the hydrogen peaks of the hydrocarbon groups contained in the boron-containing compound (B) that overlap with the hydrogen peak derived from the methylene groups of PVA to obtain the peak area (area K). Then, the area L was calculated by subtracting the number of hydrogen atoms of the hydrocarbon group of the boron-containing compound (B) that overlaps with the hydrogen peak of the methylene group derived from PVA from the area K. The values ​​obtained by these methods were substituted into the following formula (5) to calculate the content (M, parts by mass) of the organic group derived from the boron-containing compound (B) per 100 parts by mass of PVA (A). The values ​​were also substituted into the following formula (6) to calculate the boron content (N, parts by mass) derived from the boron-containing compound (B) per 100 parts by mass of PVA (A). In the following formulas (5) and (6), O is the number of hydrogen atoms of the hydrocarbon group contained in the boron-containing compound (B) that does not overlap with the peak of PVA, P is the number of boron atoms per molecule of the boron-containing compound (B), and Q is the formula weight of the organic group of the boron-containing compound (B). Then, the respective values ​​calculated were substituted into formula (7) to calculate the boron element content (b t , % by mass were calculated. Note that formulas (5), (6), and (7) are used when unmodified PVA is used, and when modified PVA is used as the raw material, formulas (5), (6), and (7) must be modified appropriately. Content of organic groups derived from boron-containing compound (B) per 100 parts by mass of PVA (A) (M, parts by mass) ={(Area J / O) / (Area L / 2)}×(Q / 44.0526)×100 (5) Content of boron element derived from boron-containing compound (B) per 100 parts by mass of PVA (A) (N, parts by mass) ={(Area J / O) / (Area L / 2)}×(10.811×P / 44.0526) ×100 (6) The boron element content (b t ,mass%) =N×1 / (100+M)×(100-TFGH) (7)

[0088] In the formula, 10.811 is the atomic weight of boron, and 44.0526 is the molecular weight per mole of the repeating unit of unmodified PVA. 1 The H-NMR chart was obtained by measuring the polarizing film of Example 1.

[0089] < Boron element concentration (b o ), boron element concentration (b i ), boron element concentration (c o ) and boron element concentration (c i ) calculation> The boron element concentration derived from the boron-containing compound (B) in the polarizing film was measured using an X-ray photoelectron spectrometer equipped with a gas cluster ion beam gun (ULVAC-PHI Inc.: PHI5000 VersaProbe II) (GCIB-XPS). The polarizing film was conditioned for more than 16 hours at approximately 23°C and 40% RH for the measurement. Sputtering was performed in an area of ​​1mm x 1mm while neutralizing under the conditions of sputter ion source Ar2500+, acceleration voltage 10keV, and current value 30nA, and X-ray photoelectron spectroscopy measurement (XPS measurement) was performed. XPS measurement was performed using monochromated Al as the X-ray source, with an X-ray spot diameter of 200μm, X-ray output of 15kV, and 50W, and five elements were selected as detection elements: carbon, boron, oxygen, iodine, and potassium. When a dichroic dye is used as the dichroic dye, elements such as nitrogen and sulfur contained in the dichroic dye must also be appropriately selected as detection elements. Next, the boron element concentration (a, atomic %) at each depth of the polarizing film was calculated using the analysis software "MultiPak" (ULVAC-PHI, Inc.) based on 284.8 eV, which is the bond energy of C-C and C-H bonds. After that, for the XPS spectrum at each depth, the bond energy due to boron in boric acid (C) and the bond energy due to boron in the boron-containing compound (B) were appropriately set, and peak separation was performed by the least squares method using a pseudo-Voigt function using the spreadsheet software "Microsoft 2010" (Microsoft Corporation). Note that a linear function calculated from the average value of the intensity of the XPS spectrum from 187 to 189 eV and the average value of the XPS spectrum from 195 to 197 was used as the baseline. In this way, the ratio (b, %) of the peak area of ​​boron derived from the boron-containing compound (B) to the sum of the peak area of ​​boron derived from boric acid (C) and the peak area of ​​boron derived from the boron-containing compound (B) was calculated, and by substituting this into the following calculation formula (8), the boron element concentration derived from the boron-containing compound (B) at each depth and the boron element concentration derived from boric acid (C) at each depth were calculated. Boron element concentration (atomic %) from boron-containing compounds (B) = a × b × 10 -2 (8) Boron element concentration (atomic %) derived from boric acid (C) =a×(100-b)×10 -2 (9)

[0090] The bond energy due to boron in the boron-containing compound (B) varies depending on the structure of the compound. Therefore, it is necessary to set the bond energy appropriately depending on the type of boron-containing compound (B). For example, when the boron-containing compound (B) is n-propylboronic acid, the bond energy is around 191.5 eV. In addition, when performing peak separation by the least squares method using the pseudo-Voigt function, the Lorentz function ratio of boric acid is set to 0.241, and 2 1 / 2 ×σ was set to 0.916. The Lorentz function ratio and half-width of the boron-containing compound (B) also change depending on the structure of the compound. Therefore, the Lorentz function ratio and 2 1 / 2 × σ must be set appropriately. When the boron-containing compound (B) is n-propylboronic acid, the Lorentz function ratio is 0.000, 2 1 / 2 ×σ was set to 0.769.

[0091] By this method, the boron element concentration (atomic %) derived from the boron-containing compound (B) and the boron element concentration (atomic %) derived from boric acid (C) at each depth from one surface to the center of the polarizing film were calculated. Specifically, the etching range was set so that the etching rate was about 16 to 26 nm / min, and a total of 14 measurements were performed while etching from one surface to the center of the polarizing film, and the boron element concentration (atomic %) derived from the boron-containing compound (B) and the boron element concentration (atomic %) derived from boric acid (C) at each measurement, that is, at each depth, were calculated. Then, the same measurement was performed from the other surface of the polarizing film, and the boron element concentration (atomic %) derived from the boron-containing compound (B) and the boron element concentration (atomic %) derived from boric acid (C) at each depth were calculated. Then, the average of the boron elemental concentration derived from the boron-containing compound (B) calculated within a range of up to 7.5% of the total thickness from the surface of the polarizing film to the inside was determined as the boron elemental concentration derived from the boron-containing compound (B) (b o, as atomic %, and the average value of the boron element concentration (atomic %) derived from boric acid (C) calculated in the said range was taken as the boron element concentration (c o , atomic %).

[0092] Also, from the center to the outside of the polarizing film, the average value of the boron element concentration derived from the boron-containing compound (B) calculated in the range up to 7.5% of the total thickness was taken as the boron element concentration (b i , atomic %), and the average value of the boron element concentration derived from boric acid (C) calculated in the said range was taken as the boron element concentration (c i , atomic %). In order to reduce errors, the measured values of the outermost surface where sputtering was not performed were excluded and the average concentrations (c o ) and (b o ) were calculated.

[0093] <Optical properties of the polarizing film> From the central parts in the width direction and the length direction of the polarizing film, a rectangular sample of 4 cm in the length direction × 2 cm in the width direction of the polarizing film was collected, and using an integrating sphere spectrophotometer V-7100 (manufactured by JASCO Corporation) and an automatic polarizing film measuring device VAP-7070S (manufactured by JASCO Corporation) equipped with a Glan-Taylor polarizer, the parallel transmittance and the cross Nicol transmittance of the polarizing film were measured. Here, the measurement wavelength range was set to 380 to 780 nm, and the transmittance when the vibration direction of the polarized light incident on the polarizing film through the Glan-Taylor polarizer was parallel to the transmission axis of the polarizing film was taken as the parallel transmittance, and the case where it was perpendicular to the transmission axis of the polarizing film was taken as the cross Nicol transmittance. Then, using the "Polarizing Film Evaluation Program" (manufactured by JASCO Corporation), visual sensitivity correction in the visible light region with a C light source and a 2° field of view was performed in accordance with JIS Z 8722 (Method for Measuring Object Color) using the aforementioned parallel transmittance and cross Nicol transmittance, and the single transmittance and the degree of polarization of the polarizing film were calculated, and these two values were obtained as the optical characteristics of the polarizing film.

[0094] <Swelling degree of the PVA film> The PVA film was cut to 5 cm x 10 cm and immersed in 1000 mL of distilled water at 30 ° C for 30 minutes. The PVA film was then removed, the moisture on the surface of the PVA film was wiped off with filter paper, and the mass of the PVA film after immersion [R (g)] was measured. The PVA film was then dried in a dryer at 105 ° C for 16 hours, and the mass of the PVA film after drying [S (g))] was measured. The swelling degree of the PVA film was calculated by substituting the value into the following formula (10). Swelling degree (%) = (R / S) × 100 (10)

[0095] [Example 1] An aqueous PVA solution was prepared containing 100 parts by mass of PVA (saponification degree 99.9%, polymerization degree 2400), 10 parts by mass of glycerin as a plasticizer, and 0.1 parts by mass of sodium polyoxyethylene lauryl ether sulfate as a surfactant, with a PVA content of 10% by mass. The aqueous PVA solution was dried on a metal roll at 80°C to obtain a film, which was then heat-treated in a hot air dryer (120°C) for 10 minutes to obtain a PVA film with a thickness of 30 μm and a swelling degree of 200%.

[0096] A sample of 5 cm wide x 9 cm long was cut from the center of the width direction of the obtained PVA film so that a range of 5 cm wide x 5 cm long could be uniaxially stretched. This sample was immersed in pure water at 30 ° C for 30 seconds and uniaxially stretched 1.1 times in the length direction to perform swelling treatment. Next, it was immersed in an aqueous solution (dyeing treatment bath) at 30 ° C containing 0.035 mass % iodine and 3.5 mass % potassium iodide for 60 seconds and uniaxially stretched 2.2 times (total 2.4 times) in the length direction to adsorb iodine. Next, it was immersed in an aqueous solution (boric acid crosslinking treatment bath) at 30 ° C containing 3.0 mass % boric acid and 3 mass % potassium iodide and uniaxially stretched 1.2 times (total 2.7 times) in the length direction. The film was then immersed in a 60°C aqueous solution (stretching bath) containing 4.0% by mass of boric acid and 6% by mass of potassium iodide, and uniaxially stretched to a total of 6.0 times in the length direction. After the stretching treatment, the film was immersed for 30 seconds in a 50°C aqueous solution (fixing bath) containing 3.0% by mass of n-propylboronic acid and 3.5% by mass of potassium iodide as the boron-containing compound (B). In the fixing treatment, the PVA film was not stretched (stretching ratio 1.0 times). Finally, the film was dried at 60°C for 240 seconds to produce a polarizing film (thickness 13 μm).

[0097] The total boron content, total potassium content, and total iodine content in the obtained polarized film were measured and found to be 4.3 mass%, 1.0 mass%, and 5.0 mass%, respectively. The moisture content in the polarized film was then calculated and found to be 10.0 mass%. 1When H-NMR was measured and analyzed, a hydrogen peak of n-propylboronic acid that did not overlap with the hydrogen peak derived from PVA appeared at 1.1 to 1.3 ppm, so this peak area (area J) was set to 5. Next, the peak area (area K) of hydrogen of the methylene group of PVA, which appeared in the range of 1.6 to 2.4 ppm, was calculated. Since the hydrogen peak of the methylene group of PVA and the hydrogen peak of the hydrocarbon group of C2 of n-propylboronic acid overlapped, the number of hydrogen atoms of the hydrocarbon group of C2 of n-propylboronic acid, 2, was subtracted from the area K to obtain the area L. When these values ​​were substituted into the above formulas (5), (6), and (7), the content of boron element derived from the boron-containing compound (B) in the polarizing film was 0.7 mass%. When the XPS spectrum of the polarizing film was measured and analyzed, the boron element concentration (b o ) is 3.1 atomic %, and the boron element concentration (c o ) was 4.6 atomic %. In addition, the boron element concentration (b i ) is 1.1 atomic percent, and the boron element concentration (c i ) was 5.7 atom %.

[0098] When the optical properties of the polarizing film were evaluated by the above-mentioned method, the single transmittance was 44.85% when the polarization degree was 99.9%.

[0099] [Examples 2 and 3, Comparative Examples 1 to 5] A polarizing film was produced in the same manner as in Example 1, except that the composition, temperature, and immersion time of the fixing treatment bath were changed as shown in Table 1, and each measurement and evaluation were carried out. 1 In the H-NMR measurement, the boron-containing compound (B) could not be detected when the accumulation number was 256, so the accumulation number was changed to 4096.

[0100] [Comparative Example 6] This is an example of a polarizing film that does not contain a boron-containing compound (B). A polarizing film was produced in the same manner as in Example 1, except that an aqueous solution (temperature: 30°C) containing 2% by mass of potassium iodide was used as the fixing treatment bath, and the immersion time in the fixing treatment bath was changed to 20 seconds, and each measurement and evaluation were performed.

[0101] [Comparative Example 7] This is an example of a polarizing film that does not contain a boron-containing compound (B). A polarizing film was produced in the same manner as in Example 1, except that an aqueous solution (temperature: 30°C) containing 2% by mass of potassium iodide was used as the fixing treatment bath, and the immersion time in the fixing treatment bath was changed to 5 seconds, and each measurement and evaluation were performed.

[0102] In addition, in Examples 2 to 3 and Comparative Examples 1 to 7, the film was immersed in an aqueous solution (dyeing bath) (temperature 30° C.) containing 100 parts by mass of potassium iodide per 1 part by mass of iodine for 60 seconds, and uniaxially stretched to 2.2 times (total 2.4 times) in the length direction to adsorb iodine. At this time, the iodine concentration and potassium iodide concentration of the dyeing bath were adjusted so that the polarization degree of the polarizing film after drying was 99.9%. In each of Examples 1 to 3 and Comparative Examples 1 to 7, the measurements and evaluations were performed on both surfaces of the polarizing film, and the results were the same. The reason why the results were the same on both surfaces of the polarizing film is presumed to be that the adsorption of the boron-containing compound (B) from the surface to the center of the PVA film proceeded in the same way on both sides during the fixing process.

[0103] [Table 1]

[0104] As shown in Table 1, the polarizing films of the present invention in Examples 1 to 3 have high polarizing performance and high single transmittance, and can meet the demand for high definition in recent electronic devices. [Explanation of symbols]

[0105] 1 surface 2 Surface part 3 center 4 Central part 5 Hydrogen peaks originating from the measurement solvent, heavy water 6 Hydrogen peak derived from methine group of PVA 7 Hydrogen peaks derived from methylene groups of PVA 8 Hydrogen peaks derived from the hydrocarbon groups contained in the boron-containing compound (B) that overlap with the hydrogen peaks derived from PVA 9 Hydrogen peaks derived from the hydrocarbon groups contained in the boron-containing compound (B) that do not overlap with the hydrogen peaks derived from PVA t o , t i , t t Thickness

Claims

1. A polarizing film comprising polyvinyl alcohol (A), at least one boron-containing compound (B) selected from the group consisting of a monoboronic acid represented by the following formula (I) and a compound capable of being converted to the monoboronic acid in the presence of water, and boric acid (C), The boron element content (b t ) is 0.3 to 2.0 mass%, the total boron element content (T) is 3.0 to 7.0 mass%, and (b t ) ratio (b t / T) is 0.10 to 0.30, The boron element concentration (b) derived from the boron-containing compound (B) in the range of up to 7.5% of the total thickness from at least one surface to the inside o %.) is 2.2 to 10.0 atomic %. 【Chemistry 1】 [In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 and the boronic acid group are connected by a boron-carbon bond.

2. The boron element concentration (b) derived from the boron-containing compound (B) in the range from the center to the outside of the polarizing film to 7.5% of the total thickness i ) is 0.5 to 2.0 atomic %, and the boron element concentration (c i 2. The polarizing film according to claim 1, wherein the atomic percentage of ZnO is 3.5 to 8.0 atomic %.

3. The boron element concentration (c) derived from boric acid (C) in the range from the center to the outside of the polarizing film to 7.5% of the total thickness i ) relative to the boron element concentration (b i ) ratio (b i / c i 3. The polarizing film according to claim 1, wherein the σ is 0.01 to 0.

25.

4. A boron element concentration (c) derived from boric acid (C) in a range of up to 7.5% of the total thickness from at least one surface of the polarizing film to the inside. o 4. The polarizing film according to claim 1, wherein the content of ZnO in the polarizing film is 3.3 to 7.8 atomic %.

5. The boron element concentration (b) derived from the boron-containing compound (B) in the range of up to 7.5% of the total thickness from at least one surface to the inside of the polarizing film is o ) is the boron element concentration (b ) derived from the boron-containing compound (B) in the range from the center to the outside of the polarizing film to 7.5% of the total thickness i 5. The polarizing film according to claim 1, wherein the polarizing film has a refractive index higher than that of the polarizing film.

6. A boron element concentration (c) derived from boric acid (C) in a range of up to 7.5% of the total thickness from at least one surface of the polarizing film to the inside. o ) is a boron element concentration (c ) derived from boric acid (C) in a range from the center to the outside of the polarizing film to 7.5% of the total thickness i 6. The polarizing film according to claim 1, wherein the polarizing film has a viscosity of 100% or more.

7. R 1 The polarizing film according to any one of claims 1 to 6, wherein is a saturated aliphatic group.

8. R 1 The polarizing film according to any one of claims 1 to 7, wherein is a linear aliphatic hydrocarbon group.

9. R 1 The polarizing film according to any one of claims 1 to 8, wherein the number of carbon atoms is 2 to 5.

10. The polarizing film according to any one of claims 1 to 9, which has a transmittance of 42% or more when the polarization degree is 99.9% or more.

11. A method for producing a polarizing film, comprising a dyeing treatment of dyeing a polyvinyl alcohol film with a dichroic dye, and a stretching treatment of uniaxially stretching the film, The method for producing a polarized film according to any one of claims 1 to 10, further comprising a treatment of immersing the film in an aqueous solution containing a boric acid crosslinking agent, and then immersing the film in an aqueous solution containing 1.5 to 5.0 mass% of a boron-containing compound (B) at 35 to 80°C.

Citation Information

Patent Citations

  • Polarizing film having superior durability and its production

    JP1989084203A

  • Iodine-based polarizer, polarizing plate, optical film, and image display device

    JP2013156621A

  • Process for Preparing Polarizer

    KR1020150052777A

  • Polarizing plate and liquid crystal display having the same

    US20140125924A1

  • Polarizing film and production method therefor

    WO2018021274A1